2015
DOI: 10.1097/bcr.0000000000000118
|View full text |Cite
|
Sign up to set email alerts
|

Postburn Neck Anterior Contracture Treatment in Children With Scar-Fascial Local Trapezoid Flaps

Abstract: One of the dramatic consequences of burns is scar contracture and deformities of the neck. Cervical contracture in children is especially dangerous, leading to face disfigurement and kyphosis; therefore, early reconstruction is indicated. Despite the existence of many various surgical techniques, the successful neck contracture treatment in pediatric patients remains a challenge for surgeons. Eleven children (aged 5 to 14 years) with postburn neck anterior contractures were studied to develop a new approach fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
5
1
2
Order By: Relevance
“…Moreover, good condition of the skin is a symptom of physical wellness and proper nutrition. Authors showed how the presence of post burn scars causes a lateral cervical flexion contracture [11]. In our study the observation of the classrooms provided relatively negative results, since the percentage of students with a correct posture was low (data not shown).…”
Section: Discussioncontrasting
confidence: 45%
“…Moreover, good condition of the skin is a symptom of physical wellness and proper nutrition. Authors showed how the presence of post burn scars causes a lateral cervical flexion contracture [11]. In our study the observation of the classrooms provided relatively negative results, since the percentage of students with a correct posture was low (data not shown).…”
Section: Discussioncontrasting
confidence: 45%
“…In the severe neck contractures, many reconstructive options are proposed including local [1, 2, 47] and free flaps [24] and combination with tissue expansion. However, in very severe cases, the donor sites can be hardly found.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 11 cases, age 5 to 14 years, post-burn anterior neck contractures were reviewed in an attempt to develop a new approach for reconstruction with local scar-fascial flaps [1]. …”
Section: Reviewmentioning
confidence: 99%
“…Hypertrophic scars and keloids of the neck occur especially after burns. These lesions can lead to head and neck function restrictions such as; decreased neck rotation, cervical intervertebral joint and spine problems, oral competence and speech difficulties etc 7,8 . Neck scars may also cause social withdrawal symptoms.…”
Section: Discussionmentioning
confidence: 99%